Analisis Banjir Faktor Penyebab Dan Prioritas Penanganan Sungai Anduonuhu - Idati, La Ode Munawal Akbar; Magribi, La Ode Muhamad; Lakawa, Irwan (Universitas Sulawesi Tenggara, 2020)
Anduonuhu Village is one of the areas in Kendari City that has been affected by flooding in the last 10 years. Data of fload events occurred in 2013 and 2017. Based on the Data of the Kendari City Enfironmental Status Report in 2010, the distribution of potential areans prone to flooding in the city of Kendari, Anduonuhu sub-district was ranked 2 (two) with an area of 359.817 ha. The purpose of this sudy is to analyze extreme rainfall over the past 10 years, to analyze the factors that cause flooding and the priority of handling the anduonuhu river. In analyzing, the autors collect data by conducting field surveys and collecting data on gydrology, tophography and land use at the study site. The results of data analysis show that extreme rainfall in the last 10 years at the study site occurred in 2013 amounted to 191.6 mm. factors causing flooding at the study site were caused by extreme rainfall inundating the Anduonuhu watershed and land use change. The priority handling is done by modeling scenarios with normalization and river embankments.